THE CONTINGENT-FIT OF CONTEXTUAL FACTORS, SUSTAINABILITY INNOVATION AND UNIT BUSINESS PERFORMANCE: A RESEARCH MODEL AND EMPIRICAL EVIDENCE - Anis, Idrianita; Elvia Rosantina Shauki (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to analyses the effect of contingent-fit between organizational contextual factors and sustainability innovation on business unit performance. This study also analyzes the contingent-fit moderating role on the relationship between innovation capability and business unit performance of unit business banking institutions in Indonesia. This study uses contingency theory as a modern system approach in measuring contingent fit. It uses a cross-sectional survey and 75 (seventy-five) items questinaire and 306 credit officers as respondents. The result shows that the contingent fit positively affects business unit performance. It plays a moderating role in the relationship between innovation capability and performance, indicated by decreasing magnitude difference in the performance of business units with high and low innovation capability. This uniqueness of the study is on the construction of the contingent-fit and the innovation capability based on knowledge sharing and utilizing new knowledge, method, and technology. This study gives practical and social implication to unit business of banking institutions.